Development of Efficient Callus Initiation of Malta (Citrus sinensis) Through Tissue Culture - Azim, Fazle; Rahman, MM; Prodhan, Shamsul H; Sikdar, Saif U; Zobayer, Nayem; Ashrafuzzaman, M (International Journal of Agricultural Research, Innovation and Technology, 2013)
The effects of different hormonal concentration on shoot formation and callus induction were studied on BARI Malta-1 (Citrus sinensis). Seeds containing seed coat and without seed coat was treated by Murashige and Skoog (MS) media supplemented with 6-benzyl adenine (BA) and Kinetin (KIN). Removal of seed coat showed an early response for shoot formation. The highest (70%) shoot formation was obtained from seeds without seed coat treated with MS basal media + BA 1.0 mg/l while KIN showed no response for shoot formation in any supplemented concentration. However, in case of callus induction internodes and apical shoot tips were used as explants and 2, 4-dichlorophenoxy acetic acid (2, 4-D) was used as callus inducing hormone. MS basal media supplemented with 2, 4-D, 2.0 mg/l showed highest (68%) callus induction. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13935 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 64-68, December, 2011